2018
DOI: 10.1111/ijag.12975
|View full text |Cite
|
Sign up to set email alerts
|

In situ TEM study on electron irradiation effects in SiO2–Na2O–B2O3 glasses

Abstract: In situ transmission electron microscopy (TEM) was used to study the electron irradiation effects of SiO 2 -Na 2 O-B 2 O 3 (SNB) glasses. Three kinds of SNB glasses were designed and fabricated with constant K (K = [SiO 2 ]/[B 2 O 3 ] molar ratio) and varying R (R = [Na 2 O]/[B 2 O 3 ] molar ratio). The electron irradiation effects were found to be significantly dependent on the value of R. Gas bubbles and small particles were observed in the bright field (BF) images of irradiated SNB glasses with sufficient N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Reviewing the literature indicates that many researchers have studied the mechanical property evolutions of ion-and electron-irradiated borosilicate glass. In order to reveal the underlying mechanisms of this issue, experiments have been carried out to study the microstructure and macrostructure changes of glass after the irradiation [5][6][7][8][9]. The obtained results showed that variations in the mechanical characteristics mainly depended on the ion species [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature indicates that many researchers have studied the mechanical property evolutions of ion-and electron-irradiated borosilicate glass. In order to reveal the underlying mechanisms of this issue, experiments have been carried out to study the microstructure and macrostructure changes of glass after the irradiation [5][6][7][8][9]. The obtained results showed that variations in the mechanical characteristics mainly depended on the ion species [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…51 Oxygen number R represents the proportion of non-bridging oxygen in the system, which can estimate the bonding degree of Si–O and Al–O skeleton, and it can be seen by combining with the formula that the smaller the value of R is, the worse the connectivity of the aluminosilicate skeleton is. 52 According to Fig. 8(b), the MCL of CASH gels decreases when Ca/Si increases, indicating that the increase of Ca 2+ is not favorable to the polymerization reaction of CASH gels.…”
Section: Resultsmentioning
confidence: 90%
“…The oxygen number R was investigated to estimate the connectivity of the aluminosilicate structure to further characterize the final structure of NASH with different Si/Al ratios. With reference to the relevant silicate glass systems, the formation of the mesh structure shows an “island-group-chain-layered-shelf” variation, and the oxygen number R can estimate the degree of Si–O and Al–O skeleton bonding, which is expressed as follows: R normalO = N normalO / N Si N O is the the number of oxygen atoms in the aluminosilicate skeleton; N Si is the number of silicon and aluminum atoms in the aluminosilicate skeleton; R O is oxygen/(silicon + aluminum).…”
Section: Resultsmentioning
confidence: 99%